Republic of Korea : 2003 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Korea. (IMF Staff Country Reports; Country Report ;, 2004)
Korea has made a spectacular recovery from the Asian crisis. Executive Directors commended this developments, and stressed the need to implement monetary and fiscal polices. They commended the structural reforms, and emphasized the need to strengthen the asset management sector. They welcomed the approval of a free trade agreement with Chile, and looked forward to further trade-opening steps in the agricultural sector. They welcome the three-year roadmap for corporate reform, which eases regulations on 'chaebol' that improve governance.